Cobalt Single Atoms Anchored on Oxygen‐Doped Tubular Carbon Nitride for Efficient Peroxymonosulfate Activation: Simultaneous Coordination Structure and Morphology Modulation. Issue 29 (25th May 2022) - Wang, Ziwei; Almatrafi, Eydhah; Wang, Han; Qin, Hong; Wang, Wenjun; Du, Li; Chen, Sha; Zeng, Guangming; Xu, Piao
Abstract: Simultaneous regulation of the coordination environment of single‐atom catalysts (SACs) and engineering architectures with efficient exposed active sites are efficient strategies for boosting peroxymonosulfate (PMS) activation. We isolated cobalt atoms with dual nitrogen and oxygen coordination (Co−N3 O1 ) on oxygen‐doped tubular carbon nitride (TCN) by pyrolyzing a hydrogen‐bonded cyanuric acid melamine–cobalt acetate precursor. The theoretically constructed Co−N3 O1 moiety on TCN exhibited an impressive mass activity of 7.61×10 5  min −1  mol −1 with high 1 O2 selectivity. Theoretical calculations revealed that the cobalt single atoms occupied a dual nitrogen and oxygen coordination environment, and that PMS adsorption was promoted and energy barriers reduced for the key *O intermediate that produced 1 O2 . The catalysts were attached to a widely used poly(vinylidene fluoride) microfiltration membrane to deliver an antibiotic wastewater treatment system with 97.5 % ciprofloxacin rejection over 10 hours, thereby revealing the suitability of the membrane for industrial applications. Abstract : A synthetic method was developed to modulate the coordination environment and regulate support architecture, thus incorporating oxygen atoms into the first shell of Co single‐atom catalysts (SACs). The high activity and 1 O2 selectivity of Co−N3 O1 correlated with an enhanced adsorption energy of peroxymonosulfate (PMS) and reduced activation barriers. As a result, the catalysts were attached to a membrane to deliver a catalytic filter with 97.5 % ciprofloxacin rejection over 10 hours.